An efficient and optimized PCR method with high fidelity for site-directed mutagenesis. - Liang, Q; Chen, L; Fulco, A J

(untitled) (Genome Research, 1995)
We have developed an efficient method for site-directed mutagenesis using two subsequential rounds of PCR. In this method, PCR conditions are optimized to favor high fidelity of Taq DNA polymerase in the presence of equimolar concentrations of MgCI2 and dNTP in the reaction mixture (pH 5.5-6.2). This method makes use of a pair of universal primers and the multiple cloning site of pUC/M13 vectors. Only one mutagenic primer is required per target site. In the second round of PCR, the 3' extension of the wild-type DNA strand is blocked by the presence of a segment of nonhomologous sequence at its 3' end, and as a consequence, the amplified, full-length DNA fragment is chiefly from the mutant strand. Furthermore, because the mutated DNA fragment has flanking restriction sites different from those of the wild-type DNA fragment, the wild-type DNA fragment is totally excluded in the step involving selective cloning of the mutant DNA fragment. This method was successfully used to introduce four, nonadjacent mutations in the 5' regulatory region of the cytochrome P450BM-3 gene. All 20 analyzed clones from these four cases of mutagenesis carried the desired mutations, and no undesired mutations were observed. We observed that the larger the number of mismatched nucleotide residues in the mutagenic primer, the higher the concentration of MgCI2 was necessary for successful PCR amplification. Our experimental results indicate that this method offers improvements in efficiency, flexibility, and fidelity.